2014
DOI: 10.1111/jfb.12428
|View full text |Cite
|
Sign up to set email alerts
|

FirstmtDNAsequencing of Volga and Ob basin taimenHucho taimen: European populations stem from a late Pleistocene expansion ofH. taimenout of western Siberia and are not intermediate toHucho hucho

Abstract: New concatenated mtDNA sequences (three genes; n = 22) of Siberian taimen Hucho taimen primarily from west Siberian and European regions of the species' range were added to 12 previously published sequences to provide a phylogeographic overview of the species. European samples show only very minor divergence from west Siberian populations, supporting a late Pleistocene expansion from Siberia into the Urals, with no particular relation to the Danube River basin huchen Hucho hucho as once hypothesized. The disju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 12 publications
4
18
0
Order By: Relevance
“…This study has demonstrated that Mongolian H. taimen represents the most upstream extent of the two previously identified major phylogroups, which means that two independent ESUs need to be recognized in conservation and management efforts in the country (Figure a). The Selenge and Shishged ESU forms part of the western phylogroup that consists of the greater Yenisei, Khatanga, Volga, and Ob river basin H. taimen , while the Onon and Kherlen ESU is part of the eastern Amur phylogroup together with Lena basin H. taimen (Froufe, Alekseyev et al, ; Maric et al, ). Certain ecological traits such as the H. taimen's large body size and propensity of mature individuals to move and disperse extensive distances particularly during the spawning season (Holčík et al, ; Matveyev, Pronin, Samusenok, & Bronte, ; Jensen et al, ; Gilroy et al, ; Kaus, Büttner et al, ) has likely contributed to the minimal genetic structure found in this long‐lived species.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study has demonstrated that Mongolian H. taimen represents the most upstream extent of the two previously identified major phylogroups, which means that two independent ESUs need to be recognized in conservation and management efforts in the country (Figure a). The Selenge and Shishged ESU forms part of the western phylogroup that consists of the greater Yenisei, Khatanga, Volga, and Ob river basin H. taimen , while the Onon and Kherlen ESU is part of the eastern Amur phylogroup together with Lena basin H. taimen (Froufe, Alekseyev et al, ; Maric et al, ). Certain ecological traits such as the H. taimen's large body size and propensity of mature individuals to move and disperse extensive distances particularly during the spawning season (Holčík et al, ; Matveyev, Pronin, Samusenok, & Bronte, ; Jensen et al, ; Gilroy et al, ; Kaus, Büttner et al, ) has likely contributed to the minimal genetic structure found in this long‐lived species.…”
Section: Discussionmentioning
confidence: 99%
“…This study has demonstrated that Mongolian H. taimen represents the most upstream extent of the two previously identified major phylogroups, which means that two independent ESUs need to be recognized in conservation and management efforts in the country (Figure 8a). The Selenge and Shishged ESU forms part of the western phylogroup that consists of the greater Yenisei, Khatanga, Volga, and Ob river basin H. taimen, while the Onon and Kherlen ESU is part of the eastern Amur phylogroup together with Lena basin H. taimen (Froufe, Alekseyev et al, 2005;Maric et al, 2014).…”
Section: Genetic Population Structure and Priorities For Conservatimentioning
confidence: 99%
See 2 more Smart Citations
“…Genetic data on European huchen are still sparse and mostly restricted to phylogenetic analysis of a few specimens in higher order systematic studies (e.g. Crespi and Fulton 2004;Shedko et al 2013) or research focused on the congener taxa, such as taimen (Hucho taimen) (Froufe et al 2005;Maric et al 2014a), lenok (Brachymystax lenok) (Xia et al 2006;Liu et al 2015), Sichuan taimen (Hucho bleekeri) (Wu 2006;Wang et al 2011), and Japanese huchen (Hucho perryi) (Oleinik and Skurikhina 2008). Some previous genetic studies on the phylogeographic structure associated with multiple broodstocks and wild populations of European huchen among major drainages provided fragmentary information about their genetic structure and variability (Geist et al 2009;Weiss et al 2011;Maric et al 2014b;Kucinski et al 2015).…”
Section: Introductionmentioning
confidence: 99%